Are liquid biopsies ready for primetime?. Issue 6 (23rd December 2018) - Emamekhoo, Hamid; Lang, Joshua M.
Abstract : There is a fundamental need for predictive and pharmacodynamic biomarkers for patients with solid tumors. New liquid biopsies hold great promise, but their clinical usefulness has yet to be defined in prospective clinical trials.